Aboriginal settlements of arid Patagonia: Preserving bio- or sociodiversity? The case of the Mapuche pastoral Cushamen Reserve - Golluscio, Rodolfo (2010)
Preservation of biodiversity can be at odds with preservation of sociodiversity, i.e., human groups with different cultures, social organization and economic activities coexisting within a region. We analyzed this problem in the Cushamen Reserve, a pastoralist Mapuche aboriginal settlement in Patagonia, Argentina. We found that the current stocking rate of domestic herbivores is twice the rangeland carrying capacity, and this overstocking has resulted in a 20-30% reduction in plant cover, productivity, floristic richness and pastoral value compared to similar sites located on neighboring capitalist farms. The potential economic income of a generic Cushamen farm (625 ha) under the current stocking rate (0.27 sheep unitsbullet operatorha-1) and productive parameters (wool and number of lambs produced per sheep each year and the number of sheep that died or were discarded per year) is above the family poverty line, but this potential may be only rarely achieved due to interannual variability of productive parameters. However, under the carrying capacity, only an improbable combination of 0.84 lambsbullet operatorsheep-1 yr-1, 5.5 kg woolbullet operatorsheep-1 yr-1 and a 16% rate of annual sheep discarding would equal the present potential income. Active policies aimed at increasing carrying capacity of the Cushamen Reserve are needed to preserve both bio- and sociodiversity.